Women Empowerment in Selected Fisheries-Related Livelihoods In Asid Gulf, Masbate, Philippines - Mahawan, Alvin M.; Velza, Jacob Frederick P.; Ibañez, Jr. , Roger Y.; Dioneda, Sr. , Ronnel R.; Belardo, Sipronio B.; Agonos, Emily M. (Future Science / FSH-PH Publications, 2022)
Women empowerment contributes to the coastal economy and dispositions to household income. This descriptive study aimed to establish women's empowerment and their roles in the overall performance of selected fisheries-related livelihood in coastal towns of Milagros, Cawayan, Placer, and Esperanza, Masbate. It was participated by 81 women beneficiaries. A structured survey questionnaire was utilized to collect information on the sociodemographic profile and adequacy level of empowerment aligned to WEAI-5DE. It was backed up with FGDs and KIIs. The data were treated through descriptive analysis techniques using frequencies and percentages. The respondents mainly belong to the reproductive age group (15-49 years old) and are married individuals (84%). They have resulted in the dismayed of occupation because respondents are mainly housewives. The present study reveals that women achieved an adequate level of control over using income and building relationships or groups within and outside the organization; hence, women are empowered. The study also focused on the need for women's empowerment along with agricultural production, access to and control of productive resources, leadership in the community, and time allocation. These gaps and impediments may be addressed when feasible vocational/TVET training programs are introduced to women, the establishment of collaboration among concerned government agencies to channel fishery products directly to the market, and the inclusion of gender sensitivity activities to lessen gender inequality in the fishery community.